The Transformative Role of Blockchain Technology in Supply Chain Management: Enhancing Risk Management, Security, and Transparency - ABA-TALIB , Khawla; ZOUINE , Abdessamad (Revue Internationale des Sciences de Gestion, 2025)
Blockchain technology has emerged as a disruptive innovation for enhancing risk management, security and transparency within supply chains across numerous industries, which drew considerable attention for its potential in revolutionizing supply chain management practices. This systematic review analyzed 282 peer-reviewed articles published between 2016 and 2024 to explore the integration of blockchain technology in supply chain management. The analysis and bibliometric techniques applied in this review highlight leading researchers, influential journals, and emerging trends in blockchain adoption within supply chains, specifically focusing on risk management, security and transparency. The findings of this research underscore blockchain's potential to strengthen supply chain resilience through the improvement of risk assessment capabilities and fostering of trust among stakeholders with an enhanced data integrity and transparency. This systematic review synthesizes empirical evidence suggesting that blockchain technology offers a robust framework to address challenges in supply chain risk management and security. It promises significant advancements in operational efficiency, reduced vulnerabilities to fraud and cyber threats, and improved overall transparency, hence, providing critical insights for researchers, practitioners, and policymakers seeking to harness blockchain's potential in enhancing supply chain resilience and security.